Charter School Closing Inequities: Do automatic closure laws target Black charter entrepreneurs and Black students?. Issue 2 (23rd February 2023) - Kingsbury, Ian; Maranto, Robert; Bradley-Dorsey, Martha
ABSTRACT: In some states, charter schools must meet inflexible, standardized performance standards to survive. Through lenses informed by Critical Race Theory, we hypothesize that charters that were established by African Americans and those which serve more African American students are more likely to close, and that state-imposed standardized closure rules exacerbate these inequities. We find that 31.9% charter schools serving predominantly African American populations close, compared to 13.7% of those serving other populations. Similarly, 31.1% of charter schools started by African Americans close compared to just 14.6% of other charters. Moreover, automatic standardized closure criteria dramatically amplify the racially disparate effects.